CSF3R T618I mutated chronic myelomonocytic leukemia: A proliferative subtype with a distinct mutational profile. (2022) - Kwon, Adelaide; Ibrahim, Ibrahim; Le, Tri; Jaso, Jesse Manuel; Weinberg, Olga; Fuda, Franklin; Chen, Weina
Abstract: Chronic myelomonocytic leukemia (CMML) is a clonal myeloid neoplasm characterized by sustained monocytosis and mutations in TET2, ASXL1, SRSF2, SETBP1, NRAS, and KRAS . We describe a rare case of CSF3R T618I mutated CMML that has a proliferative phenotype, myelodysplasia, and additional mutations in ASXL1, SETBP1, KRAS, and PTPN11 . Comparing the clinicopathologic features of this case to previously reported cases of CSF3R T618I mutated CMML and CSF3R non-T618I mutated CMML, CSF3R T618I seems to define a unique proliferative subtype of CMML with a distinct mutational profile. The diagnostic challenges and molecular pathogenesis associated with this case are also briefly discussed.